Informal Settlement Upgrading in South Africa: A Preliminary Regenerative Perspective - Anita Venter (Sustainability, 2019)
Informal settlement upgrading is commonly practised worldwide, but often in technical ways, paying little attention to the physical environment. Regenerative development provides an ecological response and emphasises human development concerns. In this paper, we adopt a social constructivist approach to investigating the meaning of construction processes and the value of regenerative development in an informal upgrading process in South Africa. We used data from 18 projects and five in-depth interviews. Our findings show how waste can be used in this process, and that regenerative development delivers houses that are better insulated and avoid some of the risks associated with houses constructed by informal settlers. The value of the project lies in the acceptance of eco-building and the development of an attachment to the physical environment. Regenerative development facilitates self-help, which in turn supports the user value of these houses. We found considerable human development linked to regenerative development. Our findings show that, in addition to providing shelter, regenerative development encourages artistry and imagination, gets members of the community to work together, promotes social empowerment, improves physical and mental health, and fosters enjoyment.